Dynamics of Islamic Consumer Behavior and Market Trends - Wibowo, Riko Adi (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aims to understand the dynamics of Islamic consumer behavior and market trends by examining the interplay of religious beliefs, cultural values, economic factors, and social dynamics within a globalized economy. Research Design and Methodology: A qualitative literature review methodology was employed, systematically examining, and synthesizing existing scholarly works on Islamic consumer behavior and market trends. Relevant academic articles, books, reports, and other scholarly sources were identified, selected, and analyzed to extract key themes and insights. Findings and Discussion: The analysis reveals that religiosity, ethical considerations, halal authenticity, and social responsibility influence Islamic consumer behavior. The halal industry has diversified beyond food to include sectors like cosmetics, pharmaceuticals, and tourism, reflecting evolving consumer preferences. Marketing strategies emphasizing Islamic values, authenticity, and cultural sensitivity are essential in engaging Muslim consumers and fostering brand loyalty. Implications: Understanding the multifaceted nature of Islamic consumer behavior is crucial for developing effective marketing strategies. Businesses must prioritize authenticity, transparency, and social responsibility in their practices. The integration of digital marketing platforms offers new opportunities for market engagement. Future research should continue to explore emerging trends, such as Islamic fintech and ethical investment, to provide deeper insights into the evolving landscape of Islamic consumerism.